Exercise to Improve Asthma Control and Lung Function in Stable Asthma: An Evidence-based Case Report - Romdhon, Abdul Rois; Abraham, Andre Thadeo; Damayanti, Triya (UI Scholars Hub, 2024)
Asthma is a heterogeneous disease with respiratory symptoms that vary over time and intensity. Exercise-induced asthma patients are advised to avoid strenuous physical activity, which can trigger bronchospasm. However, appropriate exercise can improve asthma control and lung function in stable asthma patients. A literature search was conducted on PubMed, COCHRANE, and EMBASE databases using Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines according to the specified eligibility criteria. Those studies were critically appraised using the Oxford Critical Appraisal Tool 4.0. Four articles were selected based on the PRISMA search strategy flowchart to assess their validity, importance, and applicability. There was a significant effect of aerobic exercise on lung function (p-value = 0.05) and asthma control (p-value = 0.004). There was a significant effect of breathing exercise on the quality-of-life outcome group (p-value <0.05) and Forced Expiratory Volume in 1 second (FEV1)% predicted (p-value <0.001). Physical exercise for 30 minutes two to three times per week or yoga exercise for 60 minutes per day for 3-5 days improves lung function and asthma control in stable asthma patients.